Puncture and internal jugular catheterization: Daily route - Nari, Gustavo; Oliva, Fernando; Prenna, Julio; Moreno, Eduardo; Olivares, Sergio (Cirugía del Uruguay, 1997)
250 cases of puncture and catheterization of the internal jugular vein are study in prospective form. A newness technique is realize by the material used, obtaining good results and demonstrating to be a simple technique with high positivity and low cost and complications level.